Evaluating the rise of electric scooters through Porter's Five Forces framework - Hambrick, Marion E.; Pond, Addison M. (London : SAGE Publications: SAGE Business Cases Originals, 2020)
In September 2017, electric scooter ride-sharing company Bird introduced its "last-mile" transportation option. Competitors Lime, Spin, Scoot, and Jump, among others, followed Bird and entered the market, and the demand for scooter ride-sharing services grew exponentially within the United States during a 12-month period. The companies received sizeable investments from venture capitalists and other investors, but also faced market challenges with a growing number of competitors, changing consumer sentiments, and increasing government regulations in cities across the nation. The Porter's Five Forces framework helps to strategically assess markets by identifying and understanding threats from new entrants and substitutes, the bargaining power of suppliers and buyers, and industry competition. This case study outlines the history of the scooter ride-sharing trend and asks readers to use the Porter's Five Forces framework to evaluate the market and factors influencing the future of this "micro-mobility" transportation sector.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Ridesharing -- United States -- Case studies; Electric vehicles -- United States -- Case studies; New business enterprises -- Finance -- Case studies; Competition -- United States -- Case studies